2019
DOI: 10.1016/j.marpolbul.2019.04.076
|View full text |Cite
|
Sign up to set email alerts
|

Foraging habits and levels of mercury in a resident population of bottlenose dolphins (Tursiops truncatus) in Bocas del Toro Archipelago, Caribbean Sea, Panama

Abstract: A small and genetically isolated bottlenose dolphin (Tursiops truncatus) population that resides year-round in the Bocas del Toro Archipelago-Panama (BDT). Photoidentification and genetic data showed that this dolphin population is highly phylopatric and is formed exclusively by individuals of the "inshore form". This study aimed to investigate the trophic ecology and mercury concentrations of bottlenose dolphin in BDT to assess their coastal habits. We collected muscle samples (n=175) of 11 potential fish pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…Foraging was the dominant activity for dolphins in this study, therefore, it is reasonable to assume that Dolphin Bay represents an important feeding habitat for dolphins. Barragán-Barrera et al (2019) found that despite the wide availability of other prey species found throughout the archipelago, the dolphins of Bocas del Toro primarily feed on dwarf round herring (Jenkinsia lamprotaenia), a small and low-calorie prey. Repeated disruption to a critical activity like foraging can result in fewer feeding events, which could lead to reduced energy acquisition for individuals.…”
Section: Effects Of Tour Boats On Dolphin Activity Patterns and Activmentioning
confidence: 99%
“…Foraging was the dominant activity for dolphins in this study, therefore, it is reasonable to assume that Dolphin Bay represents an important feeding habitat for dolphins. Barragán-Barrera et al (2019) found that despite the wide availability of other prey species found throughout the archipelago, the dolphins of Bocas del Toro primarily feed on dwarf round herring (Jenkinsia lamprotaenia), a small and low-calorie prey. Repeated disruption to a critical activity like foraging can result in fewer feeding events, which could lead to reduced energy acquisition for individuals.…”
Section: Effects Of Tour Boats On Dolphin Activity Patterns and Activmentioning
confidence: 99%
“…Ten of the samples showed analytical differences above 10%. Because each sample mass was too small to conduct more than two analyses, they could not be considered (Barragán‐Barrera et al, 2019; Seco et al, 2019; Vélez et al, 2021). We suspect this was due to the samples not being well homogenized.…”
Section: Resultsmentioning
confidence: 99%
“…In the lab and following Vélez et al (2021), skin samples were left to alcohol evaporate and then were homogenized and freeze‐dried for later analysis. Total‐mercury (THg) concentrations of skin were measured using a solid sample atomic absorption spectrometer AMA‐254 (Advanced Altec Mercury Analyzer) as described in Barragán‐Barrera et al (2019). At least two replicates of 1–2 g dry weight (dw) were analyzed for each homogenized and lyophilized sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, nuclear and mitochondrial DNA analyses indicate this population is isolated from others in the Caribbean, including the neighboring population of bottlenose dolphins in Costa Rica located 35 km away from the Bocas del Toro archipelago (Barragán- Barrera et al, 2017). Because the small dolphin community of Dolphin Bay shows such high site fidelity, they have become the main target for dolphin watching activities in the area, resulting in the largest dolphin watching fleet in Panama (May-Collado et al, 2012, 2019.…”
Section: Study Areamentioning
confidence: 99%